2009
DOI: 10.2528/pierc09052201
|View full text |Cite
|
Sign up to set email alerts
|

Full-Wave Investigations of a Probe-Excited Rectangular Ring Antenna by Method of Moments With RWG Basis Functions

Abstract: Radiation pattern, impedance characteristics, and gain of a probe-excited rectangular ring antenna are investigated by the Method of Moments with the Rao-Wilton-Glisson (RWG-MoM) basis functions. The analysis is carried out for different lengths and positions of the probe as well as various lengths, widths and heights of the ring. In addition, the distribution of the surface current is also illustrated. Consequently, the suitable parameters are determined. It is obvious that the proposed antenna offers a bidir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Many authors have found a transverse electromagnetic (TEM) field distribution across the probe aperture is a reasonable approximation for simulations of coaxial probes [1][2][3][4][5][6][7]. Therefore, a coaxial probe feeding a patch antenna can be viewed as a mode-converter which converts the TEM mode across the probe aperture into the parallel plate modes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have found a transverse electromagnetic (TEM) field distribution across the probe aperture is a reasonable approximation for simulations of coaxial probes [1][2][3][4][5][6][7]. Therefore, a coaxial probe feeding a patch antenna can be viewed as a mode-converter which converts the TEM mode across the probe aperture into the parallel plate modes.…”
Section: Introductionmentioning
confidence: 99%
“…It is regarded as the most accurate probe feeding model for both the radiation pattern and the input impedance simulations as all the propagating and evanescent parallel plate modes are included [1][2][3][4][5][6][7]. However, magnetic-frill model requires special treatment of the probe exciting source, very dense meshes or subgridding (subcell) techniques in FEM and FDTD solvers [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Linear polarized bidirectional antennas [2]- [3] have been studied and introduced. However, polarization mismatch becomes a problem when the antennas are not aligned in practical application.…”
Section: Introductionmentioning
confidence: 99%
“…The cell shape is approximated by a circle where omnidirectional antenna plays a vital role to employ at the base station [2]. However, for some specific application that requires the long-range service area such as point-to-point communication between the buildings, when the mobiles move along the confined paths such as street, highways, tunnels, and corridors, for these environments, a unidirectional or bidirectional antennas are more suitable than the omnidirectional one to serve these demands [3][4][5][6]. The omnidirectional monopole antenna is modified by adding different shapes of reflectors such as planar reflector [7], corner reflectors [8,9], curved reflectors [10], ring reflectors [11], and others to obtain the unidirectional or bidirectional beams.…”
Section: Introductionmentioning
confidence: 99%